Akupresur, Mual ,Nyeri, Kemoter EKTIVITAS AKUPRESUR TERHADAP PENURUNAN MUAL MUNTAH AKIBAT KEMOTERAPI DAN NYERI PADA PASIEN KANKER PAYUDARA - Endah Panca Lydia F (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2018)
Chemotherapy is one of the therapies for cancer patients that cause some side effects, one of them is nausea and vomiting. Nausea and vomiting are still felt by patients even though they take antiemetics. Nausea dan vomiting can cause fluid and electrolyte imbalance. In other side, pain is the most clinical mannifestation in cancer patients that can reduce their quality of life if not properly managed. Acupressure therapy is one of the complementary therapies to reduce nausea and vomiting due to chemotherapy and pain. The aim of this study was to analysis the effectiveness of acupressure in decreasing nausea-vomiting and pain due to chemotherapy effect in breast cancer patients.This quasi experimental study was involved 16 respondents. Acupressure given by used an acupressure wristband for 1-4 days after chemotherapy. Nausea-vomiting and pain levels were measured pre-post acupressure through the questionnaire by telemonitoring method. Furthermore, the data were analyzed using paired t-test for nausea vomiting and Wilcoxon for pain. The results of this study there were significant differences nausea-vomiting and pain score before and after the acupressure intervention with a p-value 0.03 and 0.026. Acupressure therapy significantly reduce chemotherapy induce nausea and vomiting and pain in breast cancer patients. Acupressure therapy is recommended as a consideration for nursing interventions in treating breast cancer patients who experience nausea and vomiting due to chemotherapy and pain so that patients can follow the chemotherapy cycle according to a predetermined schedule and improve their quality of life. Keywords: acupressure, nausea and vomiting, pain, chemotherapy, breast cancer.